Quantification of Sunscreen Ethylhexyl Triazone in Topical Skin-Care Products by Normal-Phase TLC/Densitometry - Anna W. Sobanska; Jaroslaw Pyzowski (The Scientific World Journal)
Ethylhexyl triazone (ET) was separated from other sunscreens such as avobenzone, octocrylene, octyl methoxycinnamate, and diethylamino hydroxybenzoyl hexyl benzoate and from parabens by normal-phase HPTLC on silica gel 60 as stationary phase. Two mobile phases were particularly effective: (A) cyclohexane-diethyl ether 1 : 1 (v/v) and (B) cyclohexane-diethyl ether-acetone 15 : 1 : 2 (v/v/v) since apart from ET analysis they facilitated separation and quantification of other sunscreens present in the formulations. Densitometric scanning was performed at 300 nm. Calibration curves for ET were nonlinear (second-degree polynomials), with R > 0.998. For both mobile phases limits of detection (LOD) were 0.03 and limits of quantification (LOQ) 0.1 μg spot−1. Both methods were validated.